O heroizmie etycznym idei słowa-czynu w poemacie Tadeusza Gajcego "Do potomnego" = Of ethical heroism and the idea of action-word in "Do potomnego" poem by Tadeusz Gajcy - Brasse, Rafał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Tadeusz Gajcy in his mission-statement article: O wawrzyn, referring indirectly to Norwid?s conception of the idea of ?action-word?, emphasized the educational aspect of literature, which, in the context of his own creative practice, denoted the hope of raising the human future in a fraternal spirit permeated by the ideas of humanism. What picture of man emerges from this poetry then? Will such a life attested by life attitude not seem a bit anachronistic usurpation in an era of postmodernism and cognitive relativism, also in the sphere of values?
Keywords: Gajcy, Tadeusz Stefan (1922-1944); heroizm etyczny; wartość - etyka; testament poetycki